2010
DOI: 10.5171/2010.474771
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Effectiveness of Famous and Non Famous Endorsers in Advertising

Abstract: This research aims to compare the persuasive effectiveness and attitudes change induced in the case of famous and non famous endorser in advertisement. An experimentation was conducted by 290 tunisian women. Our empirical results showed that the non celebrity spokesperson was more credible and generated more favourable attitudes towards advertising, brand and purchase intent than celebrity spokesperson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Recently, Gaied and Rached () found that non‐celebrity endorsements sometimes have more persuasive power in the advertisement of some product types compared to celebrity endorsements. This finding highlights the importance of source credibility compared to the attractiveness or “fame” of the endorser (Gaied and Rached, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gaied and Rached () found that non‐celebrity endorsements sometimes have more persuasive power in the advertisement of some product types compared to celebrity endorsements. This finding highlights the importance of source credibility compared to the attractiveness or “fame” of the endorser (Gaied and Rached, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Gaied and Rached () found that non‐celebrity endorsements sometimes have more persuasive power in the advertisement of some product types compared to celebrity endorsements. This finding highlights the importance of source credibility compared to the attractiveness or “fame” of the endorser (Gaied and Rached, ). In the current study, we examine how the brain activation generated by non‐celebrity advertisements may differ from celebrity advertisements (and in contrast to rational advertising appeals, e.g., linguistic descriptions of products) when judging product attractiveness and generating buying intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Partnering with the right celebrity will help the brand generate interest and intended responses like building the trust and relationship (Pandey, 2011). Celebrity endorsed commercials can cause more positive attitude (Gan, 2006), persuasive (Gaied & Rached, 2010), likeability, and purchase (Parmar & Patel, 2015) While unfamiliar celebrity endorsement had a little impact in persuading consumer make a to purchase (McCormick, 2016). Advertisers use celebrities to build and relate the brand or product image with the celebrity's lifestyle.…”
Section: Introduction 11 Research Backgroundmentioning
confidence: 99%
“…Meaning Transfer Model se fundamenta en que los famosos añaden valor mediante el proceso de transferencia de significado en contraste con los modelos o actores anónimos ya que "celebrities deliver meanings of extra subtlety, depth, and power" (McCracken 1989: 315). Asimismo, la literatura que ha analizado la presencia de los famosos en publicidad ha utilizado, por lo general, el modelo de la credibilidad de la fuente (Ohanian, 1990) desconocido es más eficaz que la hecha por un famoso (Biswas et al, 2006;Eisend & Langner, 2010;Gaied & Rached, 2010).…”
Section: Marco Teórico Y Preguntas De Investigación 21 El Uso De Pounclassified